Manajemen Pengelolaan Kegiatan Belajar Mengajar Berbasis Syariah di SD KUTAB Imam Syafi’i Brebes - Muhammad Raihan; Mohamad Maftuh Fauzi (EBISMAN eBisnis Manajemen, 2026)
This study aims to analyze the management of sharia-based teaching and learning activities at SD KUTTAB Imam Syafi’i Brebes, including the processes of planning, implementation, and evaluation of learning, as well as the application of sharia values in daily classroom activities. This research employed a quantitative approach, with data collected through observation, documentation, and questionnaires distributed to relevant parties. The data were analyzed descriptively to provide an objective overview of the implementation of sharia-based learning management at the school.The results indicate that the management of teaching and learning activities at SD KUTTAB Imam Syafi’i Brebes has systematically implemented the main management functions, namely planning, implementation, and evaluation. The learning process integrates sharia values such as honesty, discipline, responsibility, trustworthiness (amanah), habituation of worship practices, and the principle of adab before knowledge. Evaluation is conducted not only on academic achievement but also on students’ attitudes and character development. Although several challenges were identified, such as differences in student characteristics and time limitations, the school has addressed them through effective coordination, time management, and administrative improvements.In conclusion, the sharia-based learning management at SD KUTTAB Imam Syafi’i Brebes has been effectively implemented and supports the achievement of educational goals that emphasize not only academic excellence but also the development of Islamic character among students.